The Q-binomial theorem and rogers-ramanujan identities - Chu, Wenchang,; Zhang, Wenlong, (Utilitas Mathematica, 2011)
The q-binomial theorem and the related convolution formulae are employed to present elementary proofs for seventeen identities of Rogers-Ramanujan type, including one that appears in Ramanujan's Lost Notebook and three new identities.